Impact of single-site axonal GABAergic synaptic events on cerebellar interneuron activity - Zorrilla de San Martin, Javier (J Gen Physiol, 2015)
Axonal ionotropic receptors are present in a variety of neuronal types, and their function has largely been associated with the modulation of axonal activity and synaptic release. It is usually assumed that activation of axonal GABA(A)Rs comes from spillover, but in cerebellar molecular layer interneurons (MLIs) the GABA source is different: in these cells, GABA release activates presynaptic GABA(A) autoreceptors (autoRs) together with postsynaptic targets, producing an autoR-mediated synaptic event. The frequency of presynaptic, autoR-mediated miniature currents is twice that of their somatodendritic counterparts, suggesting that autoR-mediated responses have an important effect on interneuron activity. Here, we used local Ca(2+) photolysis in MLI axons of juvenile rats to evoke GABA release from individual varicosities to study the activation of axonal autoRs in single release sites. Our data show that single-site autoR conductances are similar to postsynaptic dendritic conductances. In conditions of high [Cl(−)](i), autoR-mediated conductances range from 1 to 5 nS; this corresponds to ∼30–150 GABA(A) channels per presynaptic varicosity, a value close to the number of channels in postsynaptic densities. Voltage responses produced by the activation of autoRs in single varicosities are amplified by a Na(v)-dependent mechanism and propagate along the axon with a length constant of 91 µm. Immunolabeling determination of synapse location shows that on average, one third of the synapses produce autoR-mediated signals that are large enough to reach the axon initial segment. Finally, we show that single-site activation of presynaptic GABA(A) autoRs leads to an increase in MLI excitability and thus conveys a strong feedback signal that contributes to spiking activity.